Examining the importance of survivin phosphorylation at Threonine 5 through its relationship with the kinase, TBK1, and the substrate, c-Src - Lishak, Jamie (2019)
As a protein that is significantly involved in many processes of cellular life and death, survivin has garnered much interest as a cancer-associated protein. It is the fourth most upregulated transcript in human cancers and it cooperates with several other proteins to aid oncogenesis. One of these is the non-receptor tyrosine kinase c-Src, which is regulated by the N-terminus of survivin. Here, we have shown that this interaction is dependent on the phosphorylation of survivin at Threonine 5. The kinase that induces this phosphorylation is thought to be the immune protein TANK-Binding Kinase 1 (TBK1) and consequently, the effects of TBK1 on survivin were also studied. TBK1 was found to reduce survivin expression in HeLa cells that had been transfected with GFP and survivin-GFP constructs, however no such effect was found on non-transfected HeLa cells (i.e. endogenous survivin) or HeLa cells transfected with survivin1-10-GFP. The experiments detailed here provide some insight into the relationships between survivin, c-Src and TBK1, with potential implications for the study of cell adhesion, apoptosis and autophagy in cancer.